Domestic Violence in American Perspective: (Kya’s Characterization in the Novel ‘Where the Crawdads Sing’) - Aam Alamsyah; Santosa Santosa; Zaenal Abidin; Sari Setiyani (Jurnal Pendidikan Bahasa, 2023)
Domestic violence is a prevalent problem, affecting children as the most vulnerable family members. It also contributes to irreparable psychological damage to human’s behavior in the future. As one of the literary works highlighting domestic violence, the novel entitled ‘Where the Crawdads Sings’ describes the suffering of the main character, who  experienced the unbearable violence committed by a mentally ill father. The present study highlights the above novel, which is frequently used as a reading source in the literature department of an English college. The study was qualitative, in which the researchers acted as the main instruments to elicit and interpret the data independently. There were three important variables illuminated in the study: a) the description of the main character, b) the values of the novel, and c) the potential use of the novel as the reading media in EFL.Despite the fact that the novel is engaging, the results show that one of the most crucial issues is the language employed in it. It is also noted that the protagonist, who is intended to be the primary character, is the one who succeeds in committing horrific crime. If the novel had been written in a more morally acceptable manner, it would not only have become a thriller for the addicts but also a valuable teaching tool and the perfect source for an EFL class, especially for adult students.